2006
DOI: 10.1080/02713680600559564
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Inhibition of Corneal Neovascularization by Photodynamic Therapy with Verteporfin

Abstract: Photodynamic therapy with verteporfin is a safe and useful procedure to reduce experimental corneal neovascularization and can be used to inhibit angiogenesis in the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This approach to measurement is consistent with that described previously. 20 Two weeks after the treatment, the animals were killed. The corneas were harvested and the upper half of the cornea, which contained the new corneal vessels, was collected from each eye.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach to measurement is consistent with that described previously. 20 Two weeks after the treatment, the animals were killed. The corneas were harvested and the upper half of the cornea, which contained the new corneal vessels, was collected from each eye.…”
Section: Methodsmentioning
confidence: 99%
“…After the application of topical proparacaine hydrochloride 0.5% (Alcaine; Alcon, Fort Worth, TX), CNV was induced using a previously described procedure with slight modification. 20 In brief, three 7-0 black silk sutures were placed radially, at midstromal depth, at the 10-, 12-, and 2-o'clock positions on the corneas of the right eyes, 3 mm from the limbus, avoiding corneal perforation. Moxifloxacin (Vigamox; Alcon, Fort Worth, TX) was instilled twice a day to minimize the risk of infection after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Corneal neovascularization is a clinical situation which seriously threatens the vision and may result from inflammation, infection, degeneration, ischemia, and trauma [22].…”
Section: Discussionmentioning
confidence: 99%
“…Verteporfin is used for the treatment of subfoveal choroidal neovascularization in patients with age-related macular degeneration, pathologic myopia, choroidal haemangioma, polypoidal choroidal vasculopathy and for patients with chronic or recurrent central serous chorioretinopathy. As already mentioned, it was shown that corneal blood vessels can be regressed by the use of systemically applied Verteporfin and subsequent photodynamic therapy [95,98,99].…”
Section: 432mentioning
confidence: 94%